Use of xanthan gum for whole cell immobilization and its impact in bioremediation - a review. (May 2022) - Dzionek, Anna; Wojcieszyńska, Danuta; Guzik, Urszula
Graphical abstract: Highlights: Xanthan gum unique properties could be used in bioremediation. Methods for xanthan cross-linking can be adjusted for biological entrapment. Previous use of xanthan as an enhancer of immobilized cells revealed its potential. Despite the not typical structure of xanthan chains, there are ways to utilize it. Abstract: Xanthan gum is one of the exo -polysaccharides produced by bacteria and is characterized by unique non-Newtonian properties. Its structure and conformation strongly depend on the fermentation conditions and such factors as temperature and ions concentration. The properties of the xanthan gum were appreciated in the controlled drug delivery but in the crosslinked form. Due to its ability to enhance the survival rate of immobilized bacteria, the potential of a crosslinked form is promising. Unfortunately, xanthan gum crosslinking procedures often require toxic substances or harsh environmental conditions, which cannot be used in the entrapment of living cells. In this study, we summarised a crosslinking method that could potentially be modified to reduce its toxicity to living cells. Moreover, this review also includes using xanthan gum in bioremediation studies and possible utilization methods to avoid carrier accumulation in the environment.